Two blocks apart : Juan Gonzales and Peter Quinn - Mayerson, Charlotte Leon (Holt, Rinehart and Winston, 1965)
Personal narratives on family, neighborhood, schools, politics, and goals by two New York City youths who, although they come from the same neighborhood, are utter strangers in their ways of life.